Overseas Communication of Chinese Online Series. From the Perspective of The Untamed (Chen Qing Ling) - WANG, ZHE; DAI, XIAOFENG (The journal of contemporary issues in business and government, 2021)
In 2019, the online series the Untamed (Chen Qing Ling), adapted from the online novel the Founder of the Devil's Path, not only achieved a good harvest of popularity and good reputation in China, but also spread to Thailand, South Korea and other places， successfully landed on Netflix, YouTube and other foreign websites, aroused attention and heated discussion in overseas markets. Now the online series the Untamed (Chen Qing Ling) becomes another successful example of overseas communication of Chinese online series. This paper is mainly aimed to interpret the Untamed (Chen Qing Ling) from the internal driving force such as elaborately polish and create high-quality scripts and overseas adaptation reduces cultural discount, and external driving force of overseas communication of online series, to analyze its success from the aspects of content and marketing, and to explore the causes of its strong overseas influence in order to provide ideas for the future overseas communication of domestic online series.